General elections in the Cape Colony, 1898-1908 - Smith, Alan John Charrington (Department of Historical Studies, 2016)
A history of parliamentary general elections can be approached in a number of different ways, but this work concentrates its attention on the results of the voting in the elections. For that reason, the Corpus has been divided into two parts. The first part deals with party politics and the elections while the second part is devoted to the systems of voting in the upper and lower house elections, the distribution of seats in the two houses of parliament, an analysis of the results of the voting in the elections and the trends in voter-support for the two major parties. The principle aim of the thesis is to provide an insight into the birth and the initial development of two-party elections in South Africa. Although the Cape Colony was only one of four British colonies which formed the Union in 1910, it was the first to evolve a system of two-party politics, and the six parliamentary general elections in the Cape Colony between 1898 and 1908 illustrate the origin and early evolution of two-party elections in South Africa. Considerable problems were encountered because the political parties in the Cape Colony were less rigid than their counterparts after 1910 and the systems of voting did not lend themselves readily to a yield of estimates of party support directly from the voting figures. Nevertheless, whilst an overall picture of the electoral trends during this crucial decade was relatively simple to ascertain, justification of the actual estimates of party support in each constituency was a different matter. Consequently, statistical appendices have been used to indicate the derivations of those figures.